A scoping review on the relationship between robotics in educational contexts and e-health - Sannicandro, Katia; De Santis, Annamaria; Bellini, Claudia; Minerva, Tommaso (Frontiers in Education, 2022)
In recent years, due to technological advancement, research has been directed to the development and analysis of resources and tools related to educational robotics with particular attention to the field of special needs and training actions aimed at learners, teachers, professionals, and families. The use of robotics in all levels of education can support the development of logical and computational thinking, interaction, communication and socialization, and the acquisition of particularly complex work practices, for example, in the medical field. The adoption of successful educational robotics training practices can be a potential tool to support rehabilitation interventions for disabilities and comprehensive training for students or future professionals in healthcare. A scoping review was conducted on the main topics “education” AND “robotics” with three specific focuses on complementary themes in educational research about ER: (1) teaching and computational thinking, (2) training in the health sector, (3) education and special needs. The authors systematically searched two online databases, Scopus and Web of Science, up to April 2022. 164 articles were evaluated, and 59 articles were analyzed, in a particular way N=33 related to computational thinking, N=15 related to e-health, and N=11 related to special needs. The following four questions guided our research: (1) What are the educational and experimental experiences conducted through robotics in transdisciplinary fields? (2) What tools and resources are most used in such experiments (educational robotics kit, humanoid robots, telepresence robots etc.)? (3) What are the constitutive elements of the experiments and studies involving robotics and health in educational contexts? (4) What are those explicitly related to students with special needs? The study presented here is part of the research project “Robotics and E-health: new Challenges for Education” (RECE) activated at the University of Modena and Reggio Emilia. RECE aims to investigate the training, educational, cognitive, and legal processes induced by the increasing diffusion of educational robotics and telemedicine in clinical and surgical contexts.